MATHEMATICAL ECONOMIC MODEL OF PRODUCTION BUDGET OPTIMIZATION AS MARKETING CONSTITUENT - Alla V. Nemova (Advanced Engineering Research)
The problem of dynamic response of the enterprises on changes in the internal and external environment on the basis of economic mathematical modeling, linear programming particularly, for the purpose of the production effectivization is considered.